Active Flows and Passive Returns - Levy, Ariel; Lieberman, Offer (Review of Finance, 2016)
Abstract The positive relationship between money flows into investment products and their return performance is an important market indicator for market practitioners and academics. This article studies the impact that active versus passive investment styles have on this relationship. We further evaluate the effects of a passive approach in two crucial stages: portfolio selection and asset allocation. We find that a passive investment style in either stage weakens the relationship between flows and returns compared with an active style. However, the investment style in the asset allocation stage has a greater effect than in the portfolio selection stage, on the relationship between flows and returns.